Strategi Pengelolaan Dana Zakat Dalam Pemberdayaan Ekonomi (Studi Baznas Kabupaten Bogor) - Astuti, Rina Andi; Nurhasan, Nurhasan; Bianda, Ryan (Universitas Labuhanbatu, 2024)
This research aims to analyze the strategy for managing BAZNAS zakat funds in Bogor Regency in economic empowerment. This research uses a qualitative descriptive method with a case study at BAZNAS Bogor Regency. Data collection through interviews, observations and documentation such as journals, financial reports and BAZNAS work plan reports for Bogor Regency. This documentation will be classified and compiled which can be used as a source by the author to analyze the zakat fund management strategy at BAZNAS Bogor Regency. Data analysis was carried out using data reduction techniques, triangulation, and drawing conclusions. The research results show that BAZNAS Bogor Regency has developed a strategy for managing zakat funds in economic empowerment which consists of three stages, namely collecting zakat funds, distributing and utilizing zakat, and monitoring zakat funds. Based on the research results, it was concluded that the strategy for managing zakat funds by BAZNAS Bogor Regency has had a positive impact on the economic empowerment of mustahik. However, there is still a need to increase community participation, improve the quality of human resources, and improve services for untouched mustahik.